2007
DOI: 10.3233/nre-2006-21402
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury occurring at work

Abstract: Introduction: Traumatic brain injury (TBI) occurring in the workplace carries major economic repercussions such as lost wages and hospital costs. Little is known about the profile of risk factors for work-related traumatic brain injury. Aims: This study describes the pre-injury demographic characteristics, injury-related characteristics and outcomes of work-related TBI and compares them with those of non work-related TBI. This study aims to provide profiles of work-related TBI to improve our understanding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 5 publications
8
64
1
1
Order By: Relevance
“…The vast majority of wrTBI studies (23 of 24; 96%) were descriptive in nature, where researchers described wrTBI in terms of its occurrence (e.g., incidence) and/or characteristics. One study added an analytic component by examining risk factors associated with wrTBI compared to non‐wrTBI [Kim et al, ]. Sixteen (67%) studies used a cross‐sectional design, seven (29%) were case series, and one (4%) used a historical cohort design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The vast majority of wrTBI studies (23 of 24; 96%) were descriptive in nature, where researchers described wrTBI in terms of its occurrence (e.g., incidence) and/or characteristics. One study added an analytic component by examining risk factors associated with wrTBI compared to non‐wrTBI [Kim et al, ]. Sixteen (67%) studies used a cross‐sectional design, seven (29%) were case series, and one (4%) used a historical cohort design.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies presented data on the severity of wrTBI cases, assessed using measures such as the Glasgow Coma Scale (GCS), Injury Severity Score (ISS), and duration of loss of consciousness and/or post‐traumatic amnesia. Specifically, two studies using hospital records showed that the majority (>70%) of hospitalized wrTBI cases were mild (i.e., GCS 13–15) [Kraus and Fife, ; Salem et al, ], while studies using trauma registry data had more severe cases as defined by the ISS [Kim et al, ; Graves et al, ]. In nine studies, the percentage of fatal cases (i.e., case fatality rates) ranged from 4% to 11%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the various injuries that can occur, occupational injury is important globally. [1][2][3][4][5][6][7] Occupational injury in economically active people causes appreciable socioeconomic and individual losses. This and the knowledge that fall injury among all occupational injuries carries a poor prognosis, have spurred efforts involving surveys that specifically address occupational injury to focus on reducing and even pre-venting injury severity.…”
Section: Introductionmentioning
confidence: 99%